2013
DOI: 10.1111/gbb.12029
|View full text |Cite
|
Sign up to set email alerts
|

High‐precision genetic mapping of behavioral traits in the diversity outbred mouse population

Abstract: Historically our ability to identify genetic variants underlying complex behavioral traits in mice has been limited by low mapping resolution of conventional mouse crosses. The newly developed Diversity Outbred (DO) population promises to deliver improved resolution that will circumvent costly fine mapping studies. The DO is derived from the same founder strains as the Collaborative Cross (CC), including three wild derived strains. Thus the DO provides more allelic diversity and greater potential for new disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 69 publications
4
139
0
1
Order By: Relevance
“…The CC, OS, and HMDP tend to show a somewhat different picture. A QTL study using the DO strains identified seven QTLs that each accounted for 11%-14% of the variance for behavioral tests related to open-field, light-dark box, tail suspension, and a visual cliff (Logan et al 2013). These effects are considerably larger than those found in humans.…”
Section: Effect Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CC, OS, and HMDP tend to show a somewhat different picture. A QTL study using the DO strains identified seven QTLs that each accounted for 11%-14% of the variance for behavioral tests related to open-field, light-dark box, tail suspension, and a visual cliff (Logan et al 2013). These effects are considerably larger than those found in humans.…”
Section: Effect Sizesmentioning
confidence: 99%
“…As a result, CSSs can detect weaker and hence more QTLs than other resources given similar sample sizes. A striking example involves results from two recent studies (Logan et al 2013;Spiezio et al 2014). One study focused on behavioral traits in DO mice and the other on metabolic traits in CSSs.…”
Section: Mapped Qtlsmentioning
confidence: 99%
“…If this "humanized" mouse model phenocopies ARPKD, then we will generate a mutant F 2 cohort using the newly described resource, Diversity Outbred mice. 39 The Diversity Outbred stock is derived from eight inbred mouse lines and is an ideal resource for high-resolution genetic mapping, obviating the need for costly fine-mapping studies. Taken together, these efforts will provide complementary strategies for identifying ARPKD-related QTL.…”
Section: Future Directionsmentioning
confidence: 99%
“…Il est inutile d'élever les souris du DO, il suffit de les commander au Jackson Laboratory. La mesure du phénotype d'intérêt chez quelques centaines d'individus du DO permet d'identifier des gènes ségrégant avec le phénotype d'intérêt (Logan et al 2013). Dans les années à venir, l'utilisation combinée du CC et du DO devrait faciliter dans l'analyse génétique des caractères complexes, un des domaines les plus difficiles de la génétique formelle (Chesler, 2014).…”
Section: Les Nouveaux Outils De La Génétique Formelleunclassified